2019
DOI: 10.1149/2.0531902jes
|View full text |Cite
|
Sign up to set email alerts
|

Review—Factors Influencing Sulfur Induced Corrosion on the Secondary Side in Pressurized Water Reactors (PWRs)

Abstract: The work presented in this review paper is part of a project to investigate corrosion degradation of steam generator (SG) tubing and tube support materials by sulfur compounds at reduced or intermediate oxidation levels (designated here as S x ). The stability of these S x species in aqueous solutions is discussed, and the electrochemical and chemical interactions between S x and metallic surfaces and the subsequent impact of these interactions on metal corrosion are reviewed. Factors influencing S x -induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 154 publications
0
21
0
Order By: Relevance
“…11,14,[16][17][18][19][20][21][22][23][24][25] There is still a debate on the origin of the beneficial role of molybdenum: does molybdenum mitigate passive film breakdown 9,11,17,[19][20][21][26][27][28][29][30][31][32][33] or promote passive film repair? 11,13,18,24,29,[31][32][33][34] Recent studies have shown that chemical/structural heterogeneities/defects, depleted in Cr 3+ , can be produced at the nanometric scale, with the pre-passivation mechanism governing the initial growth of the surface oxide film. [35][36][37] Nanoscale compositional heterogeneities were also inferred from studies of mature passive films 16,38 and can be considered as weak points at the origin of the subsequent loss of stability.…”
mentioning
confidence: 99%
“…11,14,[16][17][18][19][20][21][22][23][24][25] There is still a debate on the origin of the beneficial role of molybdenum: does molybdenum mitigate passive film breakdown 9,11,17,[19][20][21][26][27][28][29][30][31][32][33] or promote passive film repair? 11,13,18,24,29,[31][32][33][34] Recent studies have shown that chemical/structural heterogeneities/defects, depleted in Cr 3+ , can be produced at the nanometric scale, with the pre-passivation mechanism governing the initial growth of the surface oxide film. [35][36][37] Nanoscale compositional heterogeneities were also inferred from studies of mature passive films 16,38 and can be considered as weak points at the origin of the subsequent loss of stability.…”
mentioning
confidence: 99%
“…It is reported that the adsorbed S species catalysis the dissolution of Ni and inhibits its passivation [13,14]. S species can be found as HSor H2S in acidic solutions and as metastable S2O3 2or stable SO4 2anions in neutral and alkaline solutions [15]. Moreover, S and Cl species, in chloride-contained solutions, can interact with the passive film/solution interface; they have a combined effect on film degradation [15,16].…”
Section: Microstructure Investigationmentioning
confidence: 99%
“…Among the various soil parameters as noted elsewhere [5], corrosive factors are the most decisive factors, which are precisely associated with the rate of corrosion failures and performance duration of the underground pipes [6]. More than one and half dozen of physicochemical and biological factors of any soil specimens affect the external pipe corrosion; some of them are soil size [7], morphology [8], type [9], aeration [10], compactness [11], temperature [12], plasticity index [13], organic matter [14], microorganism [15], pH [16], redox potential [17], water-retaining capacity [18], resistivity [19], chloride [20], and sulfate/sulfide content [21,22]. Among these corrosive soil factors, the latter six are the most evaluative and crucial factors for assessing the corrosive degree of soils to the underground water pipes, as described in the literature [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%